See beyond the seen: ischemic cardiomyopathy with diagnostic dilemma - Er, Elise Lay Ze; Johar MJ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Cardiomyopathy can have different aetiologies. Patient may present with typical symptoms of acute heart failure or ischemic chest pain, depending on the underlying aetiologies. It is the responsibility of the treating physician to find out the cause as prompt treatment could possibly alter the prognosis of the patient, but at the same time bearing in mind other possible diagnosis apart from the one which is obvious. In this case, we present a lady who came with breathlessness and no chest pain. She was tachycardic and tachypnoeic upon arrival and her electrocardiogram (ECG) showed ischemic changes in the inferior and lateral leads. Bedside echocardiogram showed dilated left ventricle. Her cardiac biomarker was raised, making an ischemic event unlikely to be excluded. She eventually succumb to her illness. The objective of this case report was to highlight the importance of keeping an open mind about the differential diagnoses available, knowing that the conditions could have overlap features.